Defective expression of adenovirus genes during early infection of undifferentiated OTF963 embryonal carcinoma cells. - Nelson, C C (1990)
Adenovirus infection was compared in F9 (OTF963) cells and cells induced to differentiate with retinoic acid, in order to study expression of early genes under the control of the reported "E1a-like factor" in F9 cells. However, not only was transcription of the viral E1a gene defective in undifferentiated cells but expression of all the other early genes was found to be reduced in OTF963 cells in comparison to differentiated cells. The defect in early gene expression was detected at the level of transcriptional initiation during the first 48 h of infection and resulted in similarly low levels of viral cytoplasmic mRNA and viral protein synthesis. Viral DNA replication was delayed and reduced. After 48 h of infection, the defect in transcription in OTF963 cells of E1a and other early genes was relieved, so that by 72 h postinfection the level of transcription was similar to that 16 h after infection of differentiated cells. At no time did adenovirus early gene expression occur independently of viral E1a. These results suggest limits to the generality and explanatory power of the hypothesis that F9 embryonal carcinoma cells contain an E1a-like factor.